Fixed Dome Type Biogas Plant for Digestion of Cattle Dung in Solid State - Shyam, M; Singh, Rajinder; Malik, R R (Journal of Agricultural Engineering, 2006)
Family size biogas plants in rural India are fed with 1:1 mixture of cattle dung and water as substrate. Regular feeding of many of those plants is often suspended due to scarcity of water during summer season, rendering the plants non-operational. Besides inconvenience in mixing water and cattle dung, the watery digested slurry discharged from the biogas plants normally requires lot of time and space for drying before transportation to fields for use as manure. The fixed dome type family size biogas plant design has been modified for feeding of cattle dung in solidstate (total solids contents 16-18%). The modified plant has been found working well throughout the country except hilly regions.